Direct determination of aluminum in low-enriched UAlx targets (UAlx-Al) by Inductively Coupled Plasma Optical Emission Spectrometry - Sabine Neusatz Guilhen; Alexandre Luiz de Souza; Marycel Elena Barboza Cotrim; Maria Aparecida Faustino Pires (Brazilian Journal of Radiation Sciences)
The production of molybdenum-99 (99Mo) using low-enriched uranium targets (< 20% 235U) dispersed in aluminum (UAlx) is a very promising strategy towards the independence in 99Mo local production. A thorough control must be performed to ensure that these targets meet the regulatory requirements to achieve the expected efficiency in the reactor. The determination of the targets’ composition is of high interest, because the distribution of Al in different phases may have an impact on the U concentration. Among the techniques used for this purpose, inductively coupled plasma optical emission spectrometry (ICP OES) stands out because of its high sensitivity and precision, allowing for simultaneous determination of several elements in a variety of samples and matrices. However, because U exhibits a complex emission spectrum, spectral interferences are prone to affect the analysis of Al, calling for time consuming preparation steps to remove the U from the matrix. This study proposes a method of direct determination of Al in UAlx targets through the selection of specific emission lines enabled by the evaluation of the associated interferences on the recovery values.